Fighting fire with fire?: an assessment of the potential threats of westerners fighting against ISIS in Syria and Iraq - Öz, Volkan (2021)
Since the Syrian Civil War started in 2011, over forty thousand foreign fighters from different parts of the world have made their way to Syria and Iraq to join various armed groups. There are three main groups of foreign fighters: firstly, pro-ISIS foreign fighters who are associated with jihadist groups like Islamic State in Iraq and Syria (ISIS); secondly, pro-regime Shiite foreign fighters who are affiliated with the Assad government; and finally, anti-ISIS Western foreign fighters, fighting with Kurdish and Christian groups against ISIS and other jihadist groups in Syria and Iraq. Anti-ISIS Western foreign fighters’ level of radicalization and use of violence have significantly increased in Syrian-Iraqi battlefields. They have actively engaged in use of firearms, explosives, urban tactics and guerrilla warfare. They have built transnational extremist connections and networks to incite and recruit like-minded individuals. Some politically oriented extremist anti-ISIS Western foreign fighters have founded their own armed groups in Syria. Some have participated in preparation for terrorist actions after returning to their home countries. This study, thus, analyzed the profiles of anti-ISIS Western foreign fighters, assessed potential threats that they might pose and concluded that far-left extremist anti-ISIS Western foreign fighters and the armed groups that they are affiliated are a serious threat to their countries of origin and international security because they have the capability and intent to conduct terrorist acts. The increasing number of recent terrorist attacks in the West has led international organizations and countries to develop policies to tackle the threat posed by foreign fighters. Many Western countries, however, have not treated anti-ISIS Western foreign fighters like their pro-ISIS counterparts. Therefore, a comprehensive policy against anti-ISIS Western foreign fighters is required. This dissertation, on this account, presented recommendations on how international organizations and Western governments should manage the issue of anti-ISIS Western foreign fighters.